Non-homogeneous persistent random walks and Lévy–Lorentz gas. (29th August 2018) - Artuso, Roberto; Cristadoro, Giampaolo; Onofri, Manuele; Radice, Mattia
Abstract: We consider transport properties for a non-homogeneous persistent random walk, that may be viewed as a mean-field version of the Lévy–Lorentz gas, namely a 1D model characterized by a fat polynomial tail of the distribution of scatterers' distance, with parameter α . By varying the value of α we have a transition from normal transport to superdiffusion, which we characterize by appropriate continuum limits.